2019
DOI: 10.1111/jdi.13037
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for painful diabetic neuropathy in secondary healthcare in Qatar

Abstract: Aims/IntroductionPainful diabetic peripheral neuropathy (PDPN) has a significant impact on the patient's quality of life. The prevalence of PDPN in the Middle East and North Africa region has been reported to be almost double that of populations in the UK. We sought to determine the prevalence of PDPN and its associated factors in type 2 diabetes mellitus patients attending secondary care in Qatar.Materials and MethodsThis was a cross‐sectional study of 1,095 participants with type 2 diabetes mellitus attendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
1
23
0
4
Order By: Relevance
“…Previously diagnosed DN was self‐reported. PDN was diagnosed using the Douleur Neuropathique en 4 (DN4) questionnaire as previously described …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously diagnosed DN was self‐reported. PDN was diagnosed using the Douleur Neuropathique en 4 (DN4) questionnaire as previously described …”
Section: Methodsmentioning
confidence: 99%
“…Diabetic neuropathy (DN) imposes a significant health and economic burden to both the patient and health care providers . DN leads to painful diabetic neuropathy (PDN) in 18% to 65%, erectile dysfunction in 53% to 73%, and diabetic foot ulcers in 2% to 17% of patients with type 2 diabetes mellitus (T2DM). One in four patients with a diabetic foot ulcer is at risk of amputation .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, simple questionnaires, such as the Douleur Neuropathique 4, can be used to differentiate neuropathic pain from nociceptive pain based on seven interview questions, assessment of hypoesthesia to touch and pinprick, and the presence of allodynia 49,50 .…”
Section: Practical Stepped Approach To the Diagnosis Of Peripheral Nementioning
confidence: 99%
“…In the MONICA/KORA Augsburg cohort from Germany, the prevalence of painful neuropathy in people with diabetes was two to three times that of people without diabetes . In a recent study from Qatar we showed that the prevalence of painful DPN was 34.5%, but 80% of participants had not previously been diagnosed or treated for DPN . Furthermore, the Arab population had the highest prevalence of painful DPN, and it was associated with smoking, obesity and being female.…”
Section: Painful Diabetic Peripheral Neuropathymentioning
confidence: 99%